Effect of Platelet Glycoprotein IIb/IIIa PLA2 Polymorphism on Severity of Pulmonary Thromboembolism - Boroujeni, Hamid Rouhi (Tanaffos, 2014)
BACKGROUND: Pulmonary thromboembolism (PTE) is among the leading causes of death following surgery and/or hospital admission. Role of thrombophilic risk factors in the etiology of PTE is well known; But not much data is available on their role in severity of PTE. The aim of this study was to investigate the role of thrombotic risk factors especially PLA2 polymorphism of platelet glycoprotein IIb/IIIa in the severity of PTE. MATERIALS AND METHODS: Genotyping from Factor-V (FVL) and prothrombin 20210A (PT20210A) mutations were shown to be significant risk factors for PTE and recurrent PTE. The plasma concentrations of platelet glycoprotein IIb/IIIa PLA2 polymorphism, presence of FVL and PT20210A mutations were studied in 37 patients with PTE. RESULTS: Eleven of these patients had recurrent PTE. Lung perfusion scans were scored according to the percentage of vascular obstruction. Patients who had a pulmonary vascular obstruction (PVO) score >50%were compared to those with PVO score<50%. There was no significant difference between patients with PVO score>50% and those with PVO score<50% with regard to the presence of FVL and PT20210A mutations. However, patients with PVO score>50% had a significantly higher frequency of platelet glycoprotein IIb/IIIaPLA2 polymorphism than those with PVO score <50%. CONCLUSION: Our data suggest that presence of PLA2 is associated with an increased risk of PTE in the Iranian population. The association between recurrent events and coinheritance of more than one thrombophilic genetic risk factor shows that such carriers are at a higher risk of PTE.